2019
DOI: 10.3892/or.2019.7207
|View full text |Cite
|
Sign up to set email alerts
|

Cucurbitacin E inhibits the Yes‑associated protein signaling pathway and suppresses brain metastasis of human non‑small cell lung cancer in a murine model

Abstract: Human non-small cell lung cancer (NSCLC) is associated with an extremely poor prognosis especially for the 40% of patients who develop brain metastasis, and few treatment strategies exist. Cucurbitacin E (CuE), an oxygenated tetracyclic triterpenoid isolated from plants particularly of the family Cucurbitaceae, has shown anti-tumorigenic properties in several types of cancer, yet the mechanism remains unclear. Yes-associated protein (YAP), a main mediator of the Hippo signaling pathway, promotes tumorigenesis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…Moreover, cucurbitacins B, E and I are shown to induce autophagy, however inhibition of autophagy can enhance cucurbitacin-induced apoptosis [481][482][483]. They also inhibit cell migration and invasion in human breast cancer MDA-MB-231 and SKBR3, NSCLC H2030-BrM3 and PC9-BrM3, and colorectal cancer COLO-205 cells [484][485][486][487], as well as angiogenesis in HUVECs [461,488].…”
Section: Cucurbitacinsmentioning
confidence: 99%
“…Moreover, cucurbitacins B, E and I are shown to induce autophagy, however inhibition of autophagy can enhance cucurbitacin-induced apoptosis [481][482][483]. They also inhibit cell migration and invasion in human breast cancer MDA-MB-231 and SKBR3, NSCLC H2030-BrM3 and PC9-BrM3, and colorectal cancer COLO-205 cells [484][485][486][487], as well as angiogenesis in HUVECs [461,488].…”
Section: Cucurbitacinsmentioning
confidence: 99%
“…Low expression of the Hippo kinase LATS1 in addition to YAP overexpression have been identified in human NSCLC and are associated with poor prognosis [ 65 , 66 ]. Many previous studies have shown that YAP plays an important role in promoting the epithelial–mesenchymal transition (EMT), drug resistance, and metastasis in NSCLC [ 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. Moreover, the role of YAP in the cancer immunity of human NSCLC has recently been explored.…”
Section: Hippo/yap Singing Pathway In Nsclcmentioning
confidence: 99%
“…The same study also found that YAP protein expression could be rescued during the knockdown of ERK1/2 depletion through forced overexpression of the ERK2 gene [ 90 ]. In addition, several studies found that the activation of YAP increases the downstream gene expression of EGFR ligands such as amphiregulin (AREG) and neuregulin 1 (NRG-1), as well as connective tissue growth factor (CTGF) and cysteine-rich angiogenic inducer 61 (CYR61), forming an autocrine loop to reinforce the MAPK signaling pathway in order to induce drug resistance and cancer metastasis [ 75 , 76 , 94 , 95 , 96 , 97 ]. Therefore, YAP has been suggested to be involved in the promotion of resistance to therapies targeting the EGFR/Ras/Raf/MEK/ERK pathway, and it represents a therapeutic target for metastatic NSCLC.…”
Section: Hippo/yap Singing Pathway In Nsclcmentioning
confidence: 99%
See 2 more Smart Citations